Design of continuous segregated polypropylene/Al2O3 nanocomposites and impact of controlled Al2O3 distribution on thermal conductivity. (April 2020) - Zhang, Xi; Xia, Xiaochao; You, Hui; Wada, Toru; Chammingkwan, Patchanee; Thakur, Ashutosh; Taniike, Toshiaki
Abstract: Control of nanoparticle distribution in polymer matrices is a key factor for designing highly conductive nanocomposites. Here, polypropylene (PP)/aluminum oxide (Al2 O3 ) nanocomposites with a continuous segregated structure were designed. Al2 O3 nanoparticles were initially distributed in the polyolefin elastomer (POE) phase of PP/POE/Al2 O3 with a co-continuous structure. Selective extraction of the POE phase provided a porous PP scaffold, whose pore walls were covered by deposited Al2 O3 nanoparticles. Subsequent compression molding made the porous scaffold tightly compacted to form uniform and dense thermal conductive networks. The thermal conductivity was compared among nanocomposites having three different types of Al2 O3 distribution. It was found that the continuous segregated distribution was far the most effective for improving the thermal conductivity, where 1.07 W/m K was achieved at an Al2 O3 loading of 27.5 vol%.